Improvement of electromechanical coupling factor and mechanical quality factor in PZT-PMN ceramics by MnO2 addition - Rungnapa Tipakontitikul (2018)
PZT-PMN ceramic system with presence of MnO2 contents were proposed and prepared using conventional sintering method as for piezoelectric transformer application. Phase formation and several dielectric and piezoelectric parameters were studied as a function of MnO2 concentration. The x-ray diffraction study revealed the tetragonal symmetry for all samples with MnO2 doping. To determine polarization, the P-E hysteresis loop were produced and the results indicated that entering of Mn 4+ ions in the ceramic structure created large amount of oxygen vacancies and the consequent was observed as displacement of the loops to E axis. The obtained optimum parameter are d33 = 119 pC/N, k p = 0.207, Qm = 1669, tan δ = 0.0101, Pr = 20 μm/cm2 and Ec = 10 kV/cm. © (2010) Trans Tech Publications.